WATER SOLUBILITY AND DIFFUSIVITY IN OLIVINE: ITS ROLE IN PLANETARY TECTONICS - Regenauer-Lieb K.; Kohl T. (My University, 2003)
New constraints on the thermodynamic equation of state of water and the predicted water fugacity dependence of OH-solubility at elevated P-T conditions along with its influence on dislocation dynamics in olivine are reviewed. Water is shown to control the style of tectonics of a planetary lithosphere by switching on highly localized weak faulting instead of a broad, slow creeping flow. The transition occurs above a water concentration of 200 ppm H/Si. We argue that this changeover in style of tectonics has important implications for the mechanics of subduction and for plate tectonics in general. Efficient recycling of water is only given if the top strong part of the lithosphere can fail and be dragged down into the mantle in a steady way. Due to different starting conditions and differences in accretion through planetismals, Venus may have never have reached a water content above 200 ppm H/Si in the upper mantle while Mars would have now left the plate tectonic regime due to fast cooling.
Keywords: Olivine